2004
DOI: 10.1021/bi049050x
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA Polymerases λ and β Show Different Efficiencies of Translesion DNA Synthesis past Abasic Sites and Alternative Mechanisms for Frameshift Generation

Abstract: Human DNA polymerases (pols) beta and lambda could promote template slippage and generate -1 frameshifts on defined heteropolymeric DNA substrates containing a single abasic site. Kinetic data demonstrated that pol lambda was more efficient than pol beta in catalyzing translesion DNA synthesis past an abasic site, particularly in the presence of low nucleotide concentrations. Moreover, pol lambda was found to generate frameshifts in two ways: first, by using a nucleotide-stabilized primer misalignment mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 24 publications
4
76
0
Order By: Relevance
“…For example, overexpression of polymerase ␤ is associated with an increased frequency of Ϫ1 frameshift events (18). Polymerase ␤ is especially prone to bypass the AP site and read the adjacent nucleotide (18,67,68). We have provided evidence that the resulting AP bulges would be quickly processed to give a Ϫ1 frameshift.…”
Section: Human Ber Excises Damaged Nucleotides Present Inmentioning
confidence: 85%
“…For example, overexpression of polymerase ␤ is associated with an increased frequency of Ϫ1 frameshift events (18). Polymerase ␤ is especially prone to bypass the AP site and read the adjacent nucleotide (18,67,68). We have provided evidence that the resulting AP bulges would be quickly processed to give a Ϫ1 frameshift.…”
Section: Human Ber Excises Damaged Nucleotides Present Inmentioning
confidence: 85%
“…The members of the X family of DNA polymerases (DNA Pols ␤, , and in eukaryotes), in particular, can insert nucleotides opposite to certain lesions (22,172). After the Y family, the X family polymerases display the next lowest replication fidelity of the six major DNA polymerase families (119).…”
Section: Other Non-y Family Dna Polymerases Capable Of Tlsmentioning
confidence: 99%
“…An equally important source of abasic DNA lesions results from the action of DNA glycosylases, such as uracil glycosylase, which excises uracil arising primarily from spontaneous deamination of cytosines (1). Although most AP sites are removed by the base excision repair (BER) 5 pathway, a small fraction of lesions persists, and DNA with AP lesions presents a strong block to DNA synthesis by replicative DNA polymerases (DNA pols) (2,3). Several studies have been performed to address the effects of AP sites on the template DNA strand on the synthetic activity of a variety of DNA pols.…”
mentioning
confidence: 99%
“…The major replicative enzyme of eukaryotic cells, DNA pol ␦, was shown to be able to bypass an AP lesion, but only in the presence of the auxiliary factor proliferating cell nuclear antigen (PCNA) and at a very reduced catalytic efficiency if compared with an undamaged DNA template (4). On the other hand, the family X DNA pols ␤ and were shown to bypass an AP site but in a very mutagenic way (5). Recent genetic evidence in Saccharomyces cerevisiae cells showed that DNA pol ␦ is the enzyme replicating the lagging strand (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation